The Effect of Giving Croton Leaf Crude Extract (Codiaeum variegatum) as an Alternative to The Antibacterial of Edwardsiella tarda in Vitro - Annisa Isti Fauziyyah; Arief Prajitno; Mohammad Fadjar; Arif Syaifurrisal; Farid Muchtar Riyadi (Department of Aquaculture, 2021)
Production problems related to aquaculture cannot be separated from diseases that can cause death in fish. Efforts to overcome the bacterial disease Edwardsiella tarda can be done by using natural materials such as the leaves of croton (Codiaeum variegatum). This study aimed to analyze the content of active compounds contained in croton leaf extract which is antibacterial against E. tarda bacteria. Inhibition test was performed by dilution method Minimum Inhibition Concentration (MIC test) and agar diffusion (disc test). The MIC test used five concentrations: 1 mg/L, 10 mg/L, 100 mg/L, 500 mg/L, and 1000 mg/L on Tryptone Soy Broth (TSB) media, while the disc test used five doses of croton leaf extract, namely: A (100 mg/L), B ( 200 mg/L), C (300 mg/L), D (400 mg/L) and E (500 mg/L), 2 controls (positive and negative), and three replications on Tryptone Soy Agar (TSA) media and incubated for 2x24 h. The positive control used chloramphenicol (5 mg/L) antibiotic. Croton leaf extract contains several compounds, namely saponins, flavonoids, tannins, steroids, and polyphenols, which are antibacterial and could kill the test bacteria with the highest average inhibition zone results obtained at a dose of E (500 mg/L) of 6.34 mm, while the lowest results were obtained at dose A (100 mg/L) of 3.12 mm.